A COMPREHENSIVE STUDY ON SOCIO-ECONOMIC ANALYSIS OF POTATO GROWERS IN KANGRA DISTRICT OF HIMACHAL PRADESH - Raina, Aditi; Sharma, Pushpak; Gupta, Garima; Balouria, Arundhati (Potato Journal, 2024)
This study investigates the socio-economic status of potato farmers in the Kangra district of Himachal Pradesh. This district was chosen specifically because it has a substantial area under potato cultivation. The required information was gathered from two potato-growing blocks in the district. The study revealed that the majority of household heads (57%) are between the ages of 16 and 40, with an average family size of five to seven people. Agriculture and livestock rearing emerge as the primary sources of income for most farms, with an average farm size of 1.76 ha, 74% of which are irrigated. During the Kharif season, vegetable crops are dominant, while potatoes are important during the Rabi season, with an average of 21.23 ha per farm. Potato productivity varies, with large farms producing 253.75 q/ha versus 246.43 q/ha on small farms. Agriculture-related earnings, or farm earnings, account for 45.2% of total farm income, with potatoes accounting for 8%, while non-farm income accounts for ~26.5%. Future research topics include investigating the impact of climate change on potato farming and evaluating the effectiveness of agricultural policies in terms of income and productivity. Further research could look into the effects of modern farming techniques on sustainability and profitability, potentially providing insights into improving agricultural practices in the region.